1994
DOI: 10.1002/hbm.460010307
|View full text |Cite
|
Sign up to set email alerts
|

Functional imaging of procedural motor learning: Relating cerebral blood flow with individual subject performance

Abstract: Changes of local synaptic activity during acquisition of a visuomotor skill were examined with positron emission tomography (PET) imaging of regional cerebral blood flow (rCBF). Eight subject learned the pursuit rotor task, a predictable tracking task, during three sequential PET scans (day 1). Subjects returned 2 days later and repeated the three pursuit trials and PET scans (day 2) after completing an extensive practice session. Control scans without movement bracketed the pursuit trials on both days to rule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(130 citation statements)
references
References 48 publications
5
123
0
1
Order By: Relevance
“…In humans, pathological degenerative processes affecting the striatum [as in Parkinson's (PD) or Huntington's (HD) diseases], or circumscribed damage to the cerebellum, have been shown to produce an impairment on various skill-learning tasks, especially in the visuomotor modality (e.g., Doyon, Gaudreau, Laforce, Castonguay, Bédard, Bédard, & Bouchard, 1997a;Ferraro, Balota, & Connor, 1993;Harrington, York Haaland, Yeo, & Marder, 1990;Heindel, Salmon, Shults, Walicke, & Butters, 1989;Saint-Cyr, Taylor, & Lang, 1988;Sanes, Dimitrov, & Hallett, 1990). These findings have been corroborated by studies with healthy control subjects using modern brain-imaging techniques such as positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) in which hemodynamic changes have been observed in the striatum and/or the cerebellum during the incremental acquisition of visuomotor skills (e.g., Doyon, Owen, Petrides, Sziklas, & Evans, 1996b;Flament, Ellermann, Kim, Ugurbil, & Ebner, 1996;Grafton, Woods, & Mike, 1994;Jenkins, Brooks, Nixon, Frackowiak, & Passingham, 1994;Rauch et al, 1997).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In humans, pathological degenerative processes affecting the striatum [as in Parkinson's (PD) or Huntington's (HD) diseases], or circumscribed damage to the cerebellum, have been shown to produce an impairment on various skill-learning tasks, especially in the visuomotor modality (e.g., Doyon, Gaudreau, Laforce, Castonguay, Bédard, Bédard, & Bouchard, 1997a;Ferraro, Balota, & Connor, 1993;Harrington, York Haaland, Yeo, & Marder, 1990;Heindel, Salmon, Shults, Walicke, & Butters, 1989;Saint-Cyr, Taylor, & Lang, 1988;Sanes, Dimitrov, & Hallett, 1990). These findings have been corroborated by studies with healthy control subjects using modern brain-imaging techniques such as positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) in which hemodynamic changes have been observed in the striatum and/or the cerebellum during the incremental acquisition of visuomotor skills (e.g., Doyon, Owen, Petrides, Sziklas, & Evans, 1996b;Flament, Ellermann, Kim, Ugurbil, & Ebner, 1996;Grafton, Woods, & Mike, 1994;Jenkins, Brooks, Nixon, Frackowiak, & Passingham, 1994;Rauch et al, 1997).…”
Section: Introductionmentioning
confidence: 82%
“…Third, evidence from animal (Brotchie, Iansek, & Horne, 1991a, 1991b, clinical (Doyon et al, 1997a(Doyon et al, , 1998Georgiou et al, 1994Georgiou et al, , 1995Georgiou et al, , 1993, and neuroimaging investigations (Doyon et al, 1997b(Doyon et al, , 1996bGrafton et al, 1994;Jenkins et al, 1994;Seitz, Roland, Bohm, Greitz, & Stone-Elander, 1990) has demonstrated that the striatum is critically involved in the late phases of learning where automatization of a skill is thought to occur. Consistent with such a notion is the absence of deficit observed in both PD groups that may result from the fact that, in the present study, subjects had not achieved automatization of the task.…”
Section: Mirror-tracing Task: Integration Of Practiced Movementsmentioning
confidence: 99%
“…Metabolic images were aligned within subjects using an automated registration algorithm (28). Images from each subject were then transformed into the stereotaxic coordinate space of Talairach and Tournoux (29) using an automated affine transformation of 12 parameters (30,31). After coregistration of all images to the Talairach coordinate space, the field of view for which data were available in all subjects extended from approximately +10 to -60 mm relative to the anterior-posterior commissural axis.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in the fMRI signal were found to last for up to 4-6 weeks, whereas expansion of TMS maps persisted only until the performance of the task had plateaued. Functional imaging studies using positron emission tomography (PET) have shown an increase in regional cerebral blood flow (rCBF) to the motor cortex, anterior frontal and inferior parietal cortex, and rostral supplementary motor area with short-to medium-term motor practice (Lang et al 1988;Grafton et al 1992Grafton et al , 1994Grafton et al , 1995Schlaug et al 1994). There have been few studies of changes in the human sensorimotor representation as a result of long-term skill acquisition and motor reinforcement over a period of years.…”
Section: Introductionmentioning
confidence: 99%